2005
DOI: 10.1086/430265
|View full text |Cite
|
Sign up to set email alerts
|

Abundance Analyses of Field RV Tauri Stars. VI. An Extended Sample

Abstract: An abundance analysis is presented and discussed for a sample of 14 RV Tauri stars. The present abundance data and those from our previous papers and by other workers are combined in an attempt to further understanding of the dust-gas separation process that afflicts many RV Tauri variables. We propose that a star's intrinsic (i.e., initial) metallicity is given by the photospheric zinc abundance. Variables warmer than about 5000 K and with an initial metallicity ½Fe /H ! À1 are affected by dust-gas separation… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
95
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(102 citation statements)
references
References 34 publications
7
95
0
Order By: Relevance
“…For the first case, the suggested scenario (Giridhar et al 2005;Venn et al 2014) is that a deep convective envelope may prevent the depletion signature to be observed. The main problem for this scenario is that it is unknown how strong the dilution is.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the first case, the suggested scenario (Giridhar et al 2005;Venn et al 2014) is that a deep convective envelope may prevent the depletion signature to be observed. The main problem for this scenario is that it is unknown how strong the dilution is.…”
Section: Discussionmentioning
confidence: 99%
“…All 7 RV Tauri stars whose orbital parameters have been measured so far show a clear disc SED, but not all of them are depleted and there are depleted objects without a dust excess. Giridhar et al (2005) have suggested that depletion is mostly observed in stars hotter than 5000 K. As the atmospheres of cooler stars have a deep convective envelope that mixes the accreted material with the whole convective part of the envelope and hence dilutes the effect of depletion. Venn et al (2014) has also suggested the same scenario to explain not depleted RV Tauri stars with a disc.…”
Section: Disc and Chemical Depletionmentioning
confidence: 99%
“…In particular, the observed depletion is generally much shallower in the W Vir stars. Only in the case of CC Lyr does it reach the extreme values more commonly seen in RV Tau stars (e.g., ≈−3.0 dex in HP Lyr and DY Ori, see Giridhar et al 2005). The RV Tau stars depleted in their refractory elements are known binaries for a large number of them, supporting the hypothesis of a circumbinary dusty disc (Rao et al 2012).…”
Section: Chemical Compositionmentioning
confidence: 72%
“…On the other hand, these authors find the signature of dust-gas separation less convincing in RX Lib and W Vir because it relies mostly on the depletion in Sc. As we discuss in more detail in the next paragraph, severe dust-gas separation has also been reported in most of the RV Tau stars (see Giridhar et al 2005, and references therein). Maas et al (2007) found a Type II Cepheid (CC Lyr) with an extreme dust-gas separation, which is larger than in any RV Tau star.…”
Section: Chemical Compositionmentioning
confidence: 81%
See 1 more Smart Citation